2009
DOI: 10.1142/s0219635209002137
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroscience of Vision-Based Grasping: A Functional Review for Computational Modeling and Bio-Inspired Robotics

Abstract: The topic of vision-based grasping is being widely studied using various techniques and with different goals in humans and in other primates. The fundamental related findings are reviewed in this paper, with the aim of providing researchers from different fields, including intelligent robotics and neural computation, a comprehensive but accessible view on the subject. A detailed description of the principal sensorimotor processes and the brain areas involved in them is provided following a functional perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…Recently, there has been a considerable interest in possible functional interactions between the dorsal and the ventral visual stream (Chinellato and Del Pobil 2009;Orban et al 2006;Sakata et al 1997). We show that synchronized beta activity exists between AIP and IT during 3D-shape discrimination.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Recently, there has been a considerable interest in possible functional interactions between the dorsal and the ventral visual stream (Chinellato and Del Pobil 2009;Orban et al 2006;Sakata et al 1997). We show that synchronized beta activity exists between AIP and IT during 3D-shape discrimination.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, recent anatomical tracer studies have found direct reciprocal connections between 3D-shape selective areas IT (area TEs) and AIP (Borra et al 2008(Borra et al , 2010. Accordingly, several authors have hypothesized that these anatomical connections are used to facilitate 3D-shape perception (Chinellato and Del Pobil 2009;Orban et al 2006). To test this possibility, we trained two rhesus monkeys to discriminate between disparity-defined concave and convex 3D shapes and recorded simultaneously in IT (TEs) and AIP during 3D-shape discrimination.…”
mentioning
confidence: 97%
“…The idea that the dorsal and ventral pathways are both involved in 3D discrimination has been suggested in the electrophysiology literature (Orban et al 2006) and in computational modeling (Chinellato and Del Pobil 2009). This connection was recently confirmed between areas IT and AIP in macaque (Verhoef et al 2011), two areas that receive direct inputs from V4 and V3A (Nakamura et al 2001;Orban et al 2006;Sakata et al 1997), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, these two frames of reference have specific functions in the vision-for-action and vision-for-perception model such that egocentric representations would be used by the dorsal stream to program and control the skilled movements needed to carry out the action, whereas conscious perception would rely on allocentric representations supported by the ventral stream [28, 29]. However, a new question arises: how they interact and combine [30]. …”
Section: Introductionmentioning
confidence: 99%